227k views
3 votes
A student is solving the system of equations below. In which line is a mistake first made?

2x + y - 2z = 23
3x + 2y + z = 11
x - y + z = -2

line 1 z = 11 + 3x + 2y
line 2 2x + y ­- 2(11 + 3x + 2y) = 23
line 3 ­-4x ­- 3y = 45
line 4 x -­ y + (11 + 3x + 2y) = ­- 2
line 5 4x + y = - ­13
line 6 ­ -2y = 32
line 7 y = ­16, x = ¾, z = ­-11/4

User Haelix
by
6.2k points

1 Answer

5 votes

Answer:

line 1

Explanation:

because

3x + 2y + z = 11 ➡ z = 11 - 3x - 2y

3x and 2y must change sign when transfer to other sid eof equation

User TheBW
by
5.7k points